تعليم اللغة العربية في العصر الر قمي - Khofiya, An-Nida Zulfatul; Fadhil, Muhammad Zaki; Apriliyanti, Nadila; Putra, Sukkan Arya (FASAHAH, 2024)
Teachers are one of the components in education, including Islamic religious education, which greatly determines the success or failure of the objectives of Islamic religious education. In the teaching and learning process, teachers not only act as transmitters of knowledge, but are also responsible for the development of students' personalities.Teachers must create a learning process in such a way that it can stimulate students to learn effectively and dynamically in fulfilling and achieving the expected goals. Islamic education is currently faced with enormous challenges because the industrial era 4.0 has not yet ended. We were shocked by the emergence of the society 5.0 era which must be faced and is a challenge in itself in the world of Islamic education. The formulation of the problem in this research is what the challenges of Islamic religious education teachers are in facing the era of society 5.0. In this era of modernization, humans are very dependent on technology. This makes technology a basic need for everyone. Not spared from thisprogress is Arabic language education. Arabic language teachers must be able to teach by utilizing ICT tools in the learning process. In this article we will review the use of Arabic language media in the digital era.